The effects of progressive low to high intensity exercise training on blood lipids and lipoprotein profiles in collegiate adolescents - Biruk Sorate (Selcuk University, 2014)
The purpose of this study was to examine the effects of progressive low to high intensity exercise training on blood lipids and lipoprotein profiles in collegiate adolescents. Twenty (20) male and female adolescents who were volunteer to participate in physical exercise program and who were studying in Jimma University College of natural science were taken as a subject. The selected subjects were evaluated the baseline blood lipids and lipoprotein profiles before starting exercise training. Registered laboratory technicians were collect a sample of 5 mL fasting venous blood from each subject just before beginning the exercise, the second and the third blood tests were performed after the 4th and 8th weeks exercise training programs respectively. The subjects assigned to an individualized training program that consisted of walking, jogging and running progressively from low to high intensity. During 8 weeks the program included three training sessions per week. Descriptive statistics were produced for each of the parameters. Paired sample T-tests was performed, to find out the significant difference in selected lipid and lipoprotein profile. The significance level was set at P lt; 0.05 for each of the statistical tests performed. The SPSS 20 software was used for the statistical analysis. The mean TC difference of male and female subjects was 39.160 mmol/L (26.61%) and 50.260 mmol/L (29.63%) respectively after exercise training. The mean TG difference of male and female subjects was 20.660 mmol/L (19.31%) and by 23.020 mmol/L (18.68%) respectively after exercise training. The mean HDL difference of male and female subjects was 28.630 mmol/L (58.29%) and 24.320 mmol/L (52.04%) respectively after exercise training. And the mean LDL difference of male and female subjects was 33.080 mmol/L (31.03%) and by 48.210 mmol/L (36.58%) respectively after exercise training. Both male and female subjects showed that a significant increment in HDL and significant decrements showed in TC and LDL but not in TG. This study showed that exercise in female subjects reduce better TC, TG and LDL level than male subjects and male subjects develop better HDL level than female subjects. To be more beneficial in blood lipids and lipoprotein changes adolescents should participate in progressive low to high intensity exercise training programs additional to their daily routine.